2022
DOI: 10.1177/00031348221096580
|View full text |Cite
|
Sign up to set email alerts
|

Breast Trauma: A Decade of Surgical Interventions And Outcomes From us Trauma Centers

Abstract: Background Traumatic breast injuries that require surgical intervention are rare and incompletely studied. The study objective was to define the incidence, mechanism/burden of injury, interventions, and outcomes after breast injuries requiring surgery nationally. Methods All patients with breast trauma necessitating surgery were identified from the National Trauma Data Bank (NTDB) (2006-2017) using ICD-9 and -10 codes, without exclusions. Demographics, injury mechanism/severity, procedures, and outcomes (morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…This data reveals that trauma patients with a traumatic breast abrasion or contusion have, on average, a higher likelihood of having additional comorbidities. This is consistent with the findings of Sargent et al in which ISS were highest after blunt breast trauma compared to penetrating [ 10 ]. Sanders et al reported in a retrospective analysis of female blunt breast trauma patients that the most common associated comorbidities included long bone fractures (45%) and rib fractures (44%) [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This data reveals that trauma patients with a traumatic breast abrasion or contusion have, on average, a higher likelihood of having additional comorbidities. This is consistent with the findings of Sargent et al in which ISS were highest after blunt breast trauma compared to penetrating [ 10 ]. Sanders et al reported in a retrospective analysis of female blunt breast trauma patients that the most common associated comorbidities included long bone fractures (45%) and rib fractures (44%) [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…These sample characteristics are similar to previous epidemiologic and self-reporting studies [ 6 - 8 ]. Although not specified in this study, the majority of traumatic breast injuries occur from MVAs [ 5 - 8 , 10 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burns were shown to have a higher mortality rate and length of hospital stay compared to blunt or penetrating trauma. 2 Despite the morbidity of these injuries, the existing literature is lacking.…”
mentioning
confidence: 99%
“…Similarly, a large nationwide study analyzing breast trauma demographics recognized that younger patients were linked to more penetrating breast injuries. 2 Patients with traumatic breast injuries may be linked to domestic violence trauma, especially penetrating breast injuries. In our study, 27% of penetrating breast injuries were documented due to domestic or partner violence.…”
mentioning
confidence: 99%